Multi-point shape optimisation of non-axisymmetric nacelles using an adjoint method - Lushington, Henry; MacManus, David G.; Tejero, Fernando; Meyer, M.; Sheaf, Christopher T. (Association Aeronautique et Astronautique de France (3AF), 2026)
Ultra-High Bypass Ratio (UHBR) aero-engines can provide specific fuel consumption benefits at the expense of potential increases in powerplant weight and drag. Designing compact nacelles through computational optimisation methods has been a way to reduce such penalties. This paper presents an adjoint optimisation framework that is used for the multi-point design of compact aero-engine nacelles at cruise and windmilling diversion conditions. A B-Spline morphing method is used to deform the nacelle geometry using surface control points. Fully viscous Computational Fluid Dynamics (CFD) calculations alongside an adjoint solver allow optimisation of the powerplant Net Propulsive Force (𝑁𝑃𝐹𝐷) or Net Vehicle Force (𝑁𝑉𝐹𝐷) through a gradient-based algorithm. Weighting factors were used to generate a Pareto front between the two operating conditions. Overall, the developed framework was successful in designing compact nacelles for cruise and diversion conditions. Additionally, the method was able to reduce computational cost by up to 8-fold for isolated configurations and by an estimated factor of about 300 for installed configurations compared to the previous state of the art. This demonstrates the potential viability of the adjoint framework for application during early stages of industrial design.
© Rolls-Royce plc.